2017
DOI: 10.5539/ibr.v10n4p77
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Task Technology Fit, Attitude and Trust on Intention to Adopt Mobile Banking: Placing the Mediating Role of Trialability

Abstract: The purpose of this study was to investigate the proposed model in which effect of trust, attitude and task technology fit are taken as independent variables and intention to m-banking adoption as dependent variable. The study also analyzes the mediating role of trialability between the independent and dependent variables. To find out how much variance each of the independent variables contribute in dependent variable, Structural equation modeling (SEM) approach is applied on the data sample of 271 respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Additionally, the study found that task characteristics significantly affect the acceptance and successful use of mobile money service interoperability. This result is the same as the one revealed by Tam & Oliveira (2016) and Changchun, Haider, & Akram (2017) which found that mobile users feel to use technology services if they support the task at hand. Therefore, mobile money interoperability enables users to smooth transfer money, reduce the time of performing transactions, do more transactions and have more access to more service providers.…”
Section: Discussion Of Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, the study found that task characteristics significantly affect the acceptance and successful use of mobile money service interoperability. This result is the same as the one revealed by Tam & Oliveira (2016) and Changchun, Haider, & Akram (2017) which found that mobile users feel to use technology services if they support the task at hand. Therefore, mobile money interoperability enables users to smooth transfer money, reduce the time of performing transactions, do more transactions and have more access to more service providers.…”
Section: Discussion Of Findingssupporting
confidence: 86%
“…Therefore, mobile money interoperability enables users to smooth transfer money, reduce the time of performing transactions, do more transactions, have more access to more services providers, and make the task easily accomplished without limitations to service providers. A study conducted by Changchun, Haider & Akram (2017) found that task technology fit significantly affects mbanking adoption. Customers are willing to adopt new technology-related products or services when that technology solves their real problems and become useful in their day to day lives.…”
Section: Network Availabilitymentioning
confidence: 99%
“…It is finally proven that attitude is significantly influenced the intention of millennials users in West Java to use mobile banking, which is led to an acceptance of H8. So me previous studies also support this significant result between attitude and intention to continue using it [13], [15], [23]. Considering that attitude is the fundamental factor to influence the intention, ultimately, those with decisive attitude intend to utilize m-banking.…”
Section: Advances In Economics Business and Management Research Volume 177mentioning
confidence: 63%
“…Studies by [34] and [25] were used to make ease of use items (6 items). For attitude (5 items) and behavioral intention (4 items), item statements were adapted from [13], [37]. The items were designed with a 7-point Likert scale (absolutely disagree until absolutely agree).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation